2019
DOI: 10.1007/s11085-019-09943-9
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of KCl and HCl on the High-Temperature Oxidation of a Fe-2.25Cr-1Mo Steel at 400 °C

Abstract: The influence of alkali-and chlorine-containing compounds on the corrosion of superheater alloys has been studied extensively. The current paper instead investigates the corrosive effects of KCl and HCl under conditions relevant to waterwall conditions. A low-alloy (Fe-2.25Cr-1Mo) steel was exposed to KCl(s), 500 vppm HCl(g) and (KCl + HCl) in the presence of 5%O 2 and 20% H 2 O at 400 °C. The results indicate that alloy chlorination by KCl occurs by an electrochemical process, involving cathodic formation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The presence of water vapor and KCl is generally understood to significantly increase the corrosion rate. This has especially been shown to be the case at lower temperature (400-500 • C) [3,54,55]. However, a study by Folkeson et al indicated that the influence of KCl in the presence of water vapor on the growth rate of fast-growing iron-rich oxide scales became less significant with temperature (the accelerating effect was not as prominent at 500 • C as at 400 • C) [3].…”
Section: Poor Corrosion Protection After Breakawaymicrostructural Evo...mentioning
confidence: 99%
“…The presence of water vapor and KCl is generally understood to significantly increase the corrosion rate. This has especially been shown to be the case at lower temperature (400-500 • C) [3,54,55]. However, a study by Folkeson et al indicated that the influence of KCl in the presence of water vapor on the growth rate of fast-growing iron-rich oxide scales became less significant with temperature (the accelerating effect was not as prominent at 500 • C as at 400 • C) [3].…”
Section: Poor Corrosion Protection After Breakawaymicrostructural Evo...mentioning
confidence: 99%
“…Gaseous chlorine-induced corrosion, where gaseous HCl or Cl 2 diffuses to and reacts with a metal surface forming iron chloride (FeCl x ). These chlorides may vaporize and diffuse to the surface towards a higher oxygen partial pressure, where it oxidizes forming a Fe-rich oxide layer at the metal-gas interface, releasing chlorine, which could react again with iron and thus, act as an intermediate or a catalyst in the corrosion process [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Another alternative for chlorine transportation is an electrochemical mechanism, which suggests that chloride ions diffuse to the metal-oxide interface instead of a gas transport of chlorine through the oxide scale [26,32].…”
mentioning
confidence: 99%